Airhead - Cabot, Meg. (New York : Point/Scholastic, 2008)
Sixteen-year-old Emerson Watts, an advanced placement student with a disdain for fashion, is the recipient of a "whole body transplant" and finds herself transformed into one of the world's most famous teen supermodels.
Keywords: Models (Persons) -- Fiction; Transplantation of organs, tissues, etc. -- Fiction; Identity -- Fiction; New York (N.Y.) -- Fiction